(untitled) (Economic and Political Thought, 2016)
Metaphors do not only describe reality; in some cases they even create it. Western social theories – inspiring political scientists – promoted a peculiar Decalogue of specific metaphors: the society as a biological system, a machine, a market, a battlefield, a legal order, a game, a theatre, a discourse, an established hierarchy and a race for life. Contrasting policy with ethics occurs with particular strength when one begins to treat the very concept of politics as a metaphor. The theory of international relations in its foundations is based on a relatively small number of categories that are by their very nature metaphors. Politics as a purposeful activity, the search for a compromise, the mechanism that maintains society as a whole, does not exist in the modern world.